Creative therapeutic interventions for clinicians to promote physical activity in older adults with a history of brain injury: a viewpoint. (2nd January 2021) - Tucker, Jenna; Beitscher, Ilana; Koc Jr., Thomas A.; Fama, Gabriella; Patel, Jinal; Friedman, Hannah
Abstract: The positive effects of physical activity on recovery after traumatic brain injury (TBI) have been thoroughly researched; however, limited knowledge exists on alternative treatment approaches to manage clients aging with a TBI. The long-term physical, cognitive and behavioral impairments that result from TBI affect physical activity. Current research supports implementation of novel approaches to promote prolonged independence and functional mobility after TBI. There is minimal evidence that evaluates group fitness, therapeutic yoga, music therapy, virtual reality and canine-assisted therapy to address the cognitive, behavioral, physical and functional changes associated with the aging TBI population. The purpose of this position article is to identify and explore creative interventions utilized by experienced clinicians that have demonstrated improved outcomes in clients aging with TBI.